Humoral Antibody Immune Response of Newcastle Disease Vaccination in Lovebirds (Agapornis roseicollis) - Martins, Gislaine Regina Vieira; Paulillo, Antonio Carlos; Schmidt , Elizabeth Moreira dos Santos; Denadai, Janine (International Journal of Poultry Science, 2013)
Clinical and immunological parameters of vaccinated lovebirds (Agapornis roseicollis) against Newcastle Disease (ND) were evaluated. Forty eight birds were distributed into four different experimental groups, vaccinated or not against ND: GI (Ulster 2C strain), GII (B1 strain), GIII (LaSota strain) and GIV (not vaccinated-control). The humoral antibody immune response was evaluated by the inhibition of hemagglutination test (HI). The LaSota strain provided higher antibody response when compared to Ulster 2C and B1 strains. No clinical signs associated with post-vaccinal reactions were observed.